MACROECONOMIC DETERMINANTS OF TAX REVENUE IN ECONOMIC COMMUNITY OF WEST AFRICAN STATES - Sanusi, Gbenga Peter; IHUARULAM, Gideon Ifeanyi; ODERINDE, L .Oladele (The European Journal of Applied Economics, 2021)
The determination of the effects of macroeconomic environment on tax revenue is very vital for every country and more so for an economic community aiming for harmonization of macroeconomic environment and ultimately integration. However, the extent to which aggregate output, inflation, and unemployment affects tax revenue in ECOWAS has been a debate in the literature. Therefore, this study empirical show how tax revenue is related to selected macroeconomic variables. The study employed panel data analysis on six ECOWAS countries with a data set on tax revenue, gross domestic product, inflation, unemployment, trade openness and exchange rate from 2005-2019. The Wald’s test and Hausman test indicated that the fixed effects regression was appropriate for the study. The results showed that, inflation was positively related to tax revenue and statistically significant at 5 percent. A unit increase in inflation leads to 0.007 percent increase in tax revenue; economic growth was also positive and statistically significant at 5 percent; a unit rise in GDP resulted in 0.78 percent rise in governmental tax revenue. Finally, Tax revenue decreases by 0.10 percent with a unit increase in unemployment. It is recommended that ECOWAS countries should carefully manage their macroeconomic environment to boost tax revenue.